Human Papillomavirus-Related Diseases in Urology: Diagnosis, Treatment, Prevention, and Clinical Considerations for Healthcare Providers - Kyu Won Lee; Amit Mani Upadhyay; Sangrak Bae (Urogenital Tract Infection, 2026)
Human papillomavirus (HPV) has long been regarded as a gynecologic pathogen, yet its disease burden in men is substantial and rapidly increasing. In Korea, the prevalence of anogenital warts in men has tripled over the past decade, penile cancer continues to rise, and HPV-positive oropharyngeal cancer (OPC) incidence in men has already exceeded that of cervical cancer in comparable high-income countries. This review reframes HPV as an urgent urological, occupational, and public health concern. Drawing primarily on the 2023 Korean Sexually Transmitted Infection (STI) Guidelines and the 2021 U.S. Centers for Disease Control and Prevention STI Treatment Guidelines, supplemented by original primary literature retrieved from PubMed, we address: (1) the male-specific epidemiological shift; (2) nonsexual and occupational transmission routes, with particular emphasis on surgical smoke; (3) evidence-based infection control in urology practice; (4) clinical management of anogenital warts; (5) male HPV vaccination policy, international comparisons, and cost-effectiveness; and (6) future research priorities including OPC prevention, HPV and male infertility, and the need for urology-specific infection control guidelines. From 2026, Korea will include 12-year-old boys in its National Immunization Program—the first gender-neutral HPV vaccination policy in Korea. This review highlights the expanding and indispensable role of urologists in HPV management and emphasizes that infection control vigilance and gender-neutral vaccination strategies are essential to reduce the mounting societal burden of HPV-related diseases. This review provides a practical framework for urologists to integrate HPV prevention, infection control, and vaccination counseling into routine clinical practice.